Analisis Struktur Biaya dan Profitabilitas Usaha Ternak Itik Pedaging (Anas Sp) di Desa Batee Puteh Kecamatan Langsa Lama Kota Langsa - Zahra, Alvina; Basriwijaya, K.M.Z.; Saragih, Faoeza Hafiz (Jurnal Penelitian Agrisamudra, 2024)
This research aims to analyze the cost structure and profitability of the broiler duck farming business (anas sp) in Batee Puteh Village, Langsa Lama District, Langsa City. The method used is a survey method. The population in this study were breeders who cultivated broiler ducks with an ownership scale of more than 100 individuals, totaling 2 people. The method used in sampling is the Census Method. The data collected includes primary data and secondary data. The research results show that the cost structure incurred by breeders consists of fixed costs of IDR 4,473,535,-/year (2.98%) and variable costs of IDR 79,369,000,-/year (52.91%). The total income received by duck breeders in Batee Puteh Village is IDR 151,200,000,-/year with a total production cost of IDR 83,842,535,-/year resulting in a profit of IDR 67,357,465,-/year and IDR 5,613,122,-/ The month with an average profit is IDR 33,678,733,-/year and IDR 2,806,561,-/month. Based on the results of the sensitivity analysis under normal conditions and after changes in production, a 5% decrease in production, a 10% increase in feed prices and a 15% decrease in cage usage costs indicate that the duck farming business in Batee Puteh Village is still feasible to run